Searching for Information On-the-Go: Understanding User Engagement with Mobile Devices. - Absar, Rafa; Halbert, Helen; O'Brien, Heather; Trumble, Allison (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2014)
Information interaction with mobile devices is becoming increasingly common, and is often an everyday method of information search for many users. This research will investigate the system, user, and contextual variables that predict user engagement with mobile search and examine the general engagement model in the more specific mobile context. L'interaction entre l'information et les appareils mobiles est de plus en plus commune, voire une méthode de recherche d'information quotidienne pour de nombreux utilisateurs. Cette étude s'intéresse au système, à l'etilisateur et aux variables contextuelles qui prédisent l'engagement de l'utilisateur lors de la recherche sur appareils mobiles et examine les modèles d'engagement généraux dans le context plus précis des appareils mobiles.